Circulating miR-200a is a novel molecular biomarker for early-stage renal cell carcinoma - Cheng Wang; Meng Ding; Yuan-Yuan Zhu; Jicheng Hu; Cuiping Zhang; Xiaolan Lu; Jingping Ge; Jun-Jun Wang; Chunni Zhang (ExRNA)
Abstract Background Circulating microRNAs (miRNAs) have been recognized as novel molecular markers for renal cell carcinoma (RCC) diagnosis. However, the clinical impact of circulating miRNA has rarely been evaluated for the early detection of RCC. Moreover, miRNAs also play important roles in regulating RCC tumorigenesis. The aim of this study is to assess the serum signatures of the epithelial–mesenchymal transition (EMT)-related miRNA-200 family in RCC patients and evaluate their diagnostic usefulness for early-stage RCC, and further explore the functions of specifically altered miRNAs that regulate pathological genes during the RCC tumorigenesis. Methods The serum levels of three miR-200 miRNAs (miR-200a, miR-200b and miR-200c) were firstly measured in 26 RCC patients and 26 noncancer controls of the training phase using quantitative real-time polymerase chain reaction (RT-qPCR). Markedly dysregulated miRNAs in RCC patients were subsequently verified by RT-qPCR in an independent validation phase that consist of 73 patients and 73 controls. Differentially expressed miRNAs were further examined in RCC urine samples and corresponding controls. Additionally, the mechanisms underlying the altered miRNAs involved in RCC tumorigenesis were also elucidated. Results Of the three examined miRNAs, only miR-200a showed consistently decreased levels in serum of the RCC patients, especially in those with stage I disease, as compared with controls (P < 0.001). MiR-200a is also frequently downregulated in RCC urine samples. Mechanistic investigations revealed that E2F3, an oncogene with strong proliferative and cell cycle regulation potential, is a direct target gene of miR-200a in RCC. E2F3 protein levels in RCC tissues and cell lines were increased and inversely associated with miR-200a levels. Upregulation of miR-200a decreased the expression of E2F3, with consequent repressed RCC cell proliferation and induced cell cycle arrest at G0/G1 phase in vitro. In contrast, inhibition of miR-200a in RCC cells resulted in increased expression of E2F3 and enhanced cell proliferation, and promoted G1/S transition. Conclusions Serum miR-200a has the potential to be served as a novel noninvasive auxiliary diagnostic biomarker for the early detection of RCC, and the identified novel molecular interaction between miR-200a and E2F3 may provide insights into novel therapies for RCC.